Saccharomyces cerevisiae-like 1 (SEC14L1) is a prognostic factor in breast cancer associated with lymphovascular invasion. (November 2018) - Sonbul, Sultan; Aleskandarany, Mohammed; Kurozumi, Sasagu; Joseph, Chitra; Toss, Michael; Diez-Rodriguez, Maria; Nolan, Christopher; Mukherjee, Abhik; Martin, Stewart; Caldas, Carlos; Ellis, Ian; Green, Andrew; et al.
Abstract Lymphovascular invasion is strongly related to breast cancer metastasis. However, the underlying mechanisms of lymphovascular invasion and its driver molecules in breast cancer remain to be defined. In this study, we explore differential expression of genes in large molecularly characterized and clinically annotated datasets of invasive breast cancer patients (n = 8056) coupled with histological review and strict definition for lymphovascular invasion status. The METABRIC series was used to identify genes associated with lymphovascular invasion, as defined using hematoxylin and eosin staining supplemented by immunohistochemistry, at the genomic/transcriptomic levels.Saccharomyces cerevisiae -like 1 (SEC14L1 ) was identified as one of the most significant genes associated with lymphovascular invasion. The prognostic significance ofSEC14L1 gene copy number and mRNA expression was further investigated in the METABRIC series and externally validated using the Breast Cancer Gene-Expression Miner v4.0. Protein expression ofSEC14L1 was also assessed using immunohistochemistry in series of early stage breast cancer using tissue microarrays.SEC14L1 gene copy number gain was significantly associated with high histological grade and poor outcome.SEC14L1 mRNA expression showed positive association with higher grade, lymph node metastasis, and poor outcome. SEC14L1 protein overexpression was significantly associated with lymphovascular invasion (p < 0.0001), higher grade (p = 0.011), HER2 positivity (p = 0.036), and shorter survival (p = 0.00075). Our findings specifySEC14L1 as an independent prognostic factor in breast cancer. Its association, at both transcriptome and protein expression levels, with lymphovascular invasion and outcome could imply an important role in tumor progression. A further mechanistic insight into its molecular roles including potential therapeutic utility is warranted.